Effectiveness of Online Training for Rural Entrepreneurs During a Global Pandemic - Lau Sie Hoe; Mohd Ariff Zabidi Manja; Vloreen Nity Mathew; Adeline Engkamat; Zalina Ibrahim; Ahmad Lutfi Anis (Research in Social Sciences and Technology, 2021)
The ability of rural entrepreneurs to cope with the COVID-19 pandemic greatly depends on their knowledge of Information and Communication Technology (ICT) to support online business. In this study, online surveys were conducted to assess the readiness and acceptance of rural entrepreneurs in adopting to the pandemic using the available technologies. Data collected were analyzed by descriptive and inferential statistics using ANOVA. Online training modules were designed based on their specific needs. Although participants indicated that their frequency and skills of using the electronic devices or applications had generally increased or improved after the training, the increment was not statistically significant (α=0.05). This indicated that while the participants, to some extent, benefited from the online training provided, there has not been a significant impact on them.